(untitled) (Revista de Medicina Clinica, 2025)
Our microbiome is shaped by multiple factors such as genetics and the immune system, diet, exposure to antimicrobials and other drugs, environmental factors or exchange/interaction with other microbiomes. Multiple studies have suggested that deregulation of the human microbiome contribute to the development of cancer. In this review, we try to elucidate which alterations in the microbiota are related with carcinogenesis; specially emphasizing in its role in lung cancer. We have analyzed a substantial body of studies, which conclude that the microbiota is a critical biomarker for tumorigenesis and cancer therapy response. It also significantly influences clinical characterization, prediction of response to specific treatments—particularly immunotherapy —and plays a key role in cancer prognosis. We ultimately concluded that the gut-lung microbiome axis is crucial for carcinogenesis. Dysbiosis is associated with prognosis. More prospective studies are needed to assess the true role of the microbiome in prognosis and response of lung cancer.